Successional patterns of fungal communities in needles of European silver fir (Abies alba Mill.) - Sieber-Canavesi, Francesca (The New phytologist, 1993)
Successions of fungal communities in mature, senescing and decomposing needles of silver fir (Abies alba Mill.) were studied at two sites in Switzerland. These were in naturally regenerated forest (Ruswil) on soils of pH 4.0 to 4.5 and in planted forest (Üetliberg) on soils of pH 6.5 to 7.0. Attached green symptomless needles of two age classes (1- to 2 and 4- to 7-yr-old), partly brown senescent needles, entirely brown needles and litter needles were collected, surface-sterilized and incubated on 2% MEA amended with 50 mgl-1 terramycin to isolate fungi from within the tissues. Litter needles were collected in nylon nets (litter collectors) placed on the ground to facilitate good litter-soil contact. One hundred and twenty species were isolated from green symptomless needles and more than 140 from litter needles. Species could be classified in three groups according to their habit: (1) endophytes of living needles, (2) colonizers and endophytic survivors in senescent tissues, newly dead attached, and litter tissues, and (3) those which colonized needle litter only. Among the frequently isolated species, only Exophiala sp. 1 and Grovesiella abieticola (Zeller & Goodding) Morelet & Gremmen belonged exclusively to the first group. Cryptocline abietina Petrak and Gloeosporidiella sp. also belonged to this group but could occasionally be isolated from fresh litter. Prominent representatives of the second group were Cytospora pinastri Fr., Hormonema dematioides Lagerb. & Melin, Rhizosphaera oudemansii Maublanc, R. macrospora Gourbière & Morelet, and Leptostroma sp, The frequency of colonization by members of this second group, for which the term 'transition-fungi' has been introduced, decreased quickly after needle fall. Transition-fungi were fully substituted within one year after needle fall by members of the third group, such as Thysanophora penicillioides (Roum.) Kendrick, Rhizoctonia sp. 1, Gliocladium penicillioides Corda, Pseudo-microdochium sp., Cylindrocladium sp. or Coleophoma cylindrospora (Desm.) v. Höhn. Successional patterns of discrete fungal populations were significantly affected by both edaphic conditions and forest management. At Ruswil, in decreasing order of frequency, Cryptocline abietina, Gloeosporidiella sp., Grovesiella abieticola and Leptostroma sp. were the dominant species in attached green needles, as were Hormonema dematioides, Cryptocline abietina, Leptostroma sp., Rhizosphaera macrospora and R. oudemansii in partly brown and entirely brown needles, and as were Thysanophora penicillioides, Rhizoctonia sp. 1 and Gliocladium penicillioides in needle litter. In contrast, fungal communities at Üetliberg were dominated by Exophiala sp. 1 and Grovesiella abieticola in attached green needles, by Cytospora pinastri and Exophiala sp. 1 in partly and entirely brown needles and by T. penicillioides, Coleophoma cylindrospora, G. penicillioides and Cytospora pinastri in litter needles. Differences in the frequency of fungal colonization of litter needles existed also between the litter collectors. However, differences were significant only for Pseudomicrodochium sp. and Cylindrocladium sp. at Ruswil. Attached green needles were collected and buried in the litter layer close to the litter collectors in an additional experiment. Species composition was the same in buried and in naturally fallen needles at Ruswil but not at Üetliberg, where Cytospora pinastri did not occur in buried needles, i.e. colonization by this most frequent transition-fungus was missed out. Conversely, Trichoderma viride was detected only in buried, not in naturally fallen needles, at Üetliberg, where it was among the most frequently isolated soil fungi. T. viride was also the only soil fungus with any potential to colonize fallen needles